English Teachers‘ Online Reading Tasks Development Process - Setiawan, I Nengah Adi; Saputra, I Nyoman Pasek Hadi; Agustini, Dewa Ayu Eka (Journal of Educational Study, 2022)
The purpose of this research was to observe two processes: 1) developing online reading tasks; and 2) integrating those tasks into online learning platforms. This research employs a descriptive qualitative design. The subject of this study was English teacher at SMAS Laboratorium Undiksha Singaraja. The data was gathered through observation and an interview guide. The data collection procedure began with an online observation and an interview. The data were analyzed according to Miles and Huberman’s (2002) framework of analysis, which includes data collection, data reduction, data visualization, and conclusion drawing. The study’s findings indicated that 1) activities were used to develop reading tasks using online learning platforms; 2) teacher used five platforms to develop online reading tasks, including WhatsApp, Google Classroom, Youtube, Kahoot, and Quizizz; and 3) the use of online platforms to develop tasks motivates students to learn, increases students’ interest in learning, and assists students in learning technology. The implication of this research is that utilizing online platforms to develop tasks benefits students’ ability to learn technology